A survey of allelic imbalance in F1 mice - Campbell, Catarina D.; Kirby, Andrew; Nemesh, James; Daly, Mark J.; Hirschhorn, Joel N. (Genome Research, 2008)
There are widespread, genetically determined differences in gene expression. However, methods that compare transcript levels between individuals are subject to trans-acting effects and environmental differences. By looking at allele-specific expression in the F1 progeny of inbred mice, we can directly test for allelic imbalance (AI), which must be due to cis-acting variants in the parental strains. We tested over one hundred genes for AI between C57Bl/6J and A/J alleles in F1 mice, including a validation set of 23 genes enriched for cis-acting variants and a second set of 92 genes whose orthologs were previously examined for AI in humans. We assayed an average of two transcribed SNPs per gene in liver, spleen, and brain from three male and three female F1 mice. In the set of 92 genes, we observed 33 genes (36%) with significant AI including genes with AI that was specific to certain tissues or transcripts. We also observed extensive tissue-specific AI, with 11 out of 92 genes (12%) having differences in AI between tissues. Interestingly, several genes with alternate transcripts have transcript-specific AI. Finally, we observed that the presence of AI in human genes was correlated to the presence of AI in the mouse orthologs (one-tailed P = 0.003), suggesting that certain genes may be more tolerant of cis-acting variation across species.
10.1101/gr.068692.107